2002
DOI: 10.1051/0004-6361:20020694
|View full text |Cite
|
Sign up to set email alerts
|

X-ray line emission from supernova ejecta fragments

Abstract: Abstract. We show that fast moving isolated fragments of a supernova ejecta composed of heavy elements should be sources of K α X-ray line emission of the SN nuclear-processed products. Supersonic motion of the knots in the intercloud medium will result in a bow-shock/knot-shock structure creation. Fast nonthermal particles accelerated by Fermi mechanism in the MHD collisionless shocks diffuse through a cold metallic knot, suffering from Coulomb losses and producing the X-ray emission. We modeled the X-ray emi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 62 publications
3
48
0
Order By: Relevance
“…Fast moving metal rich fragments of supernova ejecta may be sources of both 6.4 keV Fe line emission as well as the high charge state Fe K-shell lines in 6.7-6.9 keV range (Bykov 2002. Cataclysmic variables and coronally active binaries comprising a numerous population in the Galactic ridge are likely X-ray sources with prominent Fe lines and were proposed by Revnivtsev et al (2009) to contribute substantially to the Galactic Center X-ray emission observed by Muno et al (2009) in deep Chandra exposure.…”
Section: Galactic Center Clustersmentioning
confidence: 99%
“…Fast moving metal rich fragments of supernova ejecta may be sources of both 6.4 keV Fe line emission as well as the high charge state Fe K-shell lines in 6.7-6.9 keV range (Bykov 2002. Cataclysmic variables and coronally active binaries comprising a numerous population in the Galactic ridge are likely X-ray sources with prominent Fe lines and were proposed by Revnivtsev et al (2009) to contribute substantially to the Galactic Center X-ray emission observed by Muno et al (2009) in deep Chandra exposure.…”
Section: Galactic Center Clustersmentioning
confidence: 99%
“…Decourchelle et al 2001). A model of X-ray line emission from fast moving ejecta fragments predicts that the fragments interacting with molecular clouds are the brightest and they could be detected from a few kpc distances (Bykov 2002).…”
Section: Have Established Thementioning
confidence: 99%
“…However, such a high column density for the molecular gas is incompatible with our estimates by nearly two orders of magnitude (see Table 1). In this scenario, the SiO enhancement could be produced by the same process that also accelerates the electrons, i.e., shocks generated by SNe [14]. Metal-rich ejecta blobs from a SN that propagates through the ambient medium create shocks, which accelerate the electrons.…”
Section: Discussionmentioning
confidence: 99%